2014
DOI: 10.1111/1346-8138.12619
|View full text |Cite
|
Sign up to set email alerts
|

Late‐onset anaphylactic reactions following i.v. cyclophosphamide pulse in a patient with systemic sclerosis and systemic lupus erythematosus overlap syndrome

Abstract: Late-onset anaphylactic reaction is a rare adverse effect of i.v. cyclophosphamide pulse (IVCY), which is caused by cyclophosphamide metabolites. We herein report a case of scleroderma and lupus overlap syndrome who developed anaphylactic reactions 3 h to 4 days after IVCY. Long time lapses between IVCY and appearance of symptoms are compatible with type I hypersensitivity to cyclophosphamide metabolites, appearing as late-onset anaphylactic reaction. Albeit unusual, this is an important anaphylactic reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Recent reports have shown that atopic patients suffering from systemic lupus erythematosus have more severe disease at diagnosis and poorer outcomes than SLE patients without atopy [ 10 ]. Furthermore, late-onset anaphylactic reactions following intravenous cyclophosphamide pulse in a patient with systemic sclerosis and systemic lupus erythematosus overlap syndrome have been also encountered [ 11 ]. Therefore, atopy seems to constitute a disease-substrate that predispose to allergic and anaphylactic reactions.…”
Section: To the Editormentioning
confidence: 99%
“…Recent reports have shown that atopic patients suffering from systemic lupus erythematosus have more severe disease at diagnosis and poorer outcomes than SLE patients without atopy [ 10 ]. Furthermore, late-onset anaphylactic reactions following intravenous cyclophosphamide pulse in a patient with systemic sclerosis and systemic lupus erythematosus overlap syndrome have been also encountered [ 11 ]. Therefore, atopy seems to constitute a disease-substrate that predispose to allergic and anaphylactic reactions.…”
Section: To the Editormentioning
confidence: 99%